Evaluation some important microbiological parameters of the carbon cycle in chernozem soils profiles - Kátai, János; Sándor, Zsolt; Tállai, Magdolna; Zsuposné Oáh, Ágnes (Acta Agraria Debreceniensis, 2016)
Some chemical and microbiological properties of the carbon cycle were investigated in three chernozem soil profiles. The soil profiles originated from a long term fertilization experiment (potato) of the University of Debrecen, Látókép, Kryvyi Rig Botanic Garden (grassland) and a large-scale farm (sunflower) of Ukraine. The results of the organic C-content, total number of bacteria, microscopical fungi, cellulose decomposing bacteria, CO2-production, microbial biomass carbon and saccharase and dehydrogenase activities were compared and evaluated with the help of correlation analyses. Close correlation was found between the organic carbon content and the number of microscopical fungi, saccharase and dehydrogenase enzymes’ activities, as well as close correlation was found between the dehydrogenase activity and microbial biomass-C and saccharase activity.